ANALISIS PENGARUH CITRA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH ( Studi Pada BANK DSP Kaliwungu ) - Ali Muhtar, 08.3502.0548; Maskur, Ali (Students Journal of Economic and Management, 2012)
Attention to customer satisfaction and consumer dissatisfaction to the attention of the companies in developing its service strategy, so that customer satisfaction is placed as the main objective of the company. Creation of customer satisfaction by Tjiptono (2005) can provide several benefits, including the relationship between companies and consumers to be harmonious, be a good foundation for repeat purchases (repeated buying), the creation of customer loyalty (customer loyalty) and form a recommendation by word of mouth (word of mouth) is beneficial for the company. This study aims to determine and analyze the presence or absence of variables influence the companys image, and quality of service to customer satisfaction Kaliwungu DSP Bank credit. Criteria of the sample is active credit customers who have become customers for at least 6 months. Samples obtained amounted to 68 people. The analysis used was multiple linear regression analysis. Validity of test results showed that all indicators is valid for all the variables while the reliability test showed that all the instruments reliable. Based on the results of regression analysis can be seen that the image quality of service and customer satisfaction has a positive effect on credit. Hypothesis test results can be seen that the image has a positive and significant impact on customer satisfaction with a standardized beta coefficient of 0.356, with a value of 0.002 Ï <0.05. While Quality of Service has a positive and significant impact on customer satisfaction with a standardized beta coefficient of 0.509, with a value of 0.000 Ï <0.05.Key words: corporate image, service quality, customer satisfaction